Modified conjoint fascial sheath suspension for the correction of severe congenital blepharoptosis in pediatric patients at different ages - Wang, Huixing; Liu, Zhaochuan; Li, Yadi; Song, Lihua; Pang, Runhui; Yang, Jianwei; Bai, Ping (Frontiers in Pediatrics, 2022)
Objective: To evaluate the surgical outcomes of modified combined fascia sheath (CFS) and levator muscle (LM) complex suspension for the correction of severe congenital blepharoptosis in pediatric patients. Methods: Pediatric patients with severe congenital blepharoptosis were enrolled form July 2017 to July 2021. All patients were divided into two groups according to their age (group A≤7 years; group B>7 years) and received CFS+LM suspension surgery. Main surgical outcome indexes include margin reflex distance 1 (MRD1) and MRD1 regression. Postoperative complications such as lagophthalmos (LAG), conjunctival prolapse, exposure keratopathy and trichiasis were documented. Results: Fifty patients (60 eyes) were enrolled, including 17 patients (18 eyes) in group A and 33 patients (42 eyes) in group B. The MRD1 in group A was 3.06±0.64 mm at 6 months after the operation, and the MRD1 in group B was 2.64±0.69 mm 6 months postoperatively which is significantly lower than that of group A (P =0. 044). At the last visit, however, the MRD1 in group A was 3.00±0.69 mm and the MRD1 in group B was 2.64±0.70 mm. There was no significant difference in MRD1 between two groups in long term (P=0.255). There were a variety of degrees of MRD1 regression, especially in the first month after the operation in both groups (both P＜0.001). There were 9 cases of postoperative complications in group A and 13 cases in group B. The overall occurrence of postoperative complications in group A was significantly lower than that in groups B (χ2 =4.413, P=0.036). Conclusions: CFS+LM suspension, a modified CFS-based surgery, is an effective treatment for severe congenital blepharoptosis in pediatric patients. Moreover, CFS+LM suspension demonstrate excellent long-term outcomes, including good movement of the eyelid, satisfied eyelid closure and fewer postoperative complications.